Statistical characterization of structural demand under earthquake loading. Part 1: Robust estimation of the central value of the data - Xavier Romão (2012)
This article is the first of two companion articles addressing the statistical characterization of seismic demand. Performance-based earthquake engineering methodologies often require the characterization of central value estimates of structural demand. Since outliers can occur in the data, central value estimates should be determined by robust estimation methods. The performance of 50 robust central value estimators is evaluated, for different sample sizes, using the chord rotation, curvature, shear force, and inter-story drift demands obtained after analyzing five reinforced concrete structures under real earthquake records scaled to several intensities. Based on the results, seven estimators are proposed for different sample sizes.